A profile of the world's young developing country migrants - David McKenzie (Institute for the Study of Labor (IZA), 2007)
Individual level census and household survey data are used to present a rich profile of the young developing migrants around the world. Youth are found to comprise a large share of all migrants, particularly in migration to other developing countries, with the probability of migration peaking in the late teens or early twenties. The paper examines in detail the age and gender composition of migrants, whether or not young migrants move alone or with a parent or spouse, their participation in schooling and work in the destination country, the types of jobs they do, and the age of return migration. The results suggest a high degree of commonality in the youth migrant experience across a number of destination countries. In particular, developing country youth tend to work in similar occupations all around the world, and are more concentrated in these occupations than older migrants or native youth. Nevertheless, there is also considerable heterogeneity amongst youth migrants: 29 percent of 18 to 24 year olds are attending school in their destination country, but another 29 percent are not working or in school. This illustrates both the potential of migration for building human capital, and the fear that lack of integration prevents it from being used.
Keywords: 330; Internationale Wanderung; Jugendliche; Altersgruppe; Geschlecht; Welt; Migranten